GENDER EQUALITY IN THE PERSPECTIVE OF ISLAM AND EDUCATION IN INDONESIA - Anastasia, Anastasia; Nurhuda, Abid; Aziz, Thariq; Ansori, Inamul Hasan (Kafa`ah: Journal of Gender Studies, 2024)
In this world, there are various problems, one of which is the problem of gender equality. Gender has recently become a hot phenomenon to be discussed. This can be seen from the fact that there are still many people who think that men are better and have a higher degree than women. So the purpose of this study is to describe the existence of gender equality in an Islamic perspective and gender equality in education in Indonesia. The method used is a literature study with careful repeated observation analysis techniques and then concluded qualitatively descriptively. The results of the study show that gender equality is highly respected in Islam and Indonesian education where from an Islamic perspective it has the same position between men and women starting from getting rewards, being servants of Allah and caliphs, achieving achievements to carrying out their obligations. Meanwhile, gender equality in the perspective of education in Indonesia is contained in Article 27 paragraphs 1 and 2 and the Law of the Republic of Indonesia Number 7 of 1994 concerning the elimination of discrimination, and Law No 20 of 2003 on the National Education System.